Hubungan antara Sistem Birokrasi dan Perilaku Birokrasi Pemerintah Kabupaten/Kota di Sulawesi Selatan* - Burhanudin Abubakar (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
This study aims at analyzing the correlation between bureaucracy system and bureaucracy behaviors. The typology of bureaucracy behavior incorporates: autocratic behavior, custodial behavior, supportive behavior, and collegial behavior. Autocratic behavior complies with selfinterests, power, authority, loyalty, obedience, and basic need fulfillment. Custodial behavior gives preferentiality to organization economic resource, solidarity, and familial relationship. Supportive behavior directs to meet the organization vision and missions. Collegial behavior tries to harmonizeperformance, familial relationship, and solidarity in achieving organization goals.The research result shows bureaucracy system causes the emergence of a transitional bureaucracy behavior. On one side, it remains practicing traditional (autocratic and custodial) behavior. On the other side, it tries to shift to modern (supportive and collegial) behavior.